Dos figuraciones literario-psicoanalíticas (PONTIFICIA UNIV CATOLICA CHILE, FAC LETRAS, 2015)
This article proposes a cross wire between literary studies and Lacanian psychoanalytic perspectives. First, through the concept of the splitting of the Ego, it seeks to understand a dialogue in Flaubert's Bouvard and Pecuchet. Second, it brings to light the absence of the object in Correr el tupido velo (2009), by Pilar Donoso, through the concepts of privation and superego.